Impact of Maternal Depression on Pregnancy and Neonatal Outcomes: A Prospective Analysis: Maternal Stress and Neonatal Outcomes - Haq, Muhammad Ikram Ul; Fatima, Samreen; Amjad, Naeem; Sheikh, Junaid Rasool (Pakistan Journal of Health Sciences, 2024)
Antenatal depression was common in pregnant women and can cause adverse maternal and neonatal outcomes. Objective: This study was conducted to evaluate the incidence of antenatal depression in hospitalized pregnant women and its association with maternal and neonatal outcomes. Methods: A prospective observational study was conducted in the Gynecology and Obstetrics and Psychiatry Department of the Hospital from July 2023 to July 2024. A total of 300 pregnant women with gestation age 240/7 weeks or less, admitted to the OBGYN department as high-risk pregnancy patients were selected by consecutive sampling. Women were presented with the Edinburgh Post Natal Depression Scale questionnaire 2-4 times every week for the entire study period along with questionnaires to personal collect data. EPDS was generally used to assess post-partum depression but we used it to evaluate perinatal depression as it is also validated for antenatal depression measurement. Patients were divided into two groups based on EDPS score, the study group contained patients at high risk of antenatal depression with a score of 10 ≤, and the comparison group contained women at low risk of depression with a score <10. Data analysis was done by SPSS version 24.0. Results: The frequency of preterm delivery was significantly higher in the study group with 40% preterm births and 23.4% early preterm births as compared to 19.1% and 12.4% in the comparison group, respectively. Similarly, birthweight was lower in the study group (40%) and low 1-minute (20%) and 5-minute Apgar scores. Multivariate regression analysis revealed an independent and significant relationship between maternal depression and preterm delivery (aOR: 3.27, 95% CI: 1.23-9.47) (p=0.030). However, no independent association was found between NICU admission and antenatal depression (aOR: 3.1, 95% CI: 1.0-5.2) (p=0.087) and risk of C-section (aOR: 0.9, 95% CI: 0.9-1.9) (p=0.731). Conclusions: Antepartum depression was a frequent condition among hospitalized pregnant women independently correlated to preterm births. Depression screening of pregnant women was recommended to prevent adverse maternal and neonatal outcomes.